The Judeo-Spanish Folk Songs in Israel: Sephardic Music and Literature between Survival and Revival - Refael, Shmuel (European journal of jewish studies, 2015)
The aim of this article is to examine the growing interest and involvement with Ladino folk songs in Israel in recent years. Its particular focus is on an overview of the stage performances, the rerecording of Ladino songs by a new generation of artists, and the inclusion of Sephardic music in the growing repertoire of Israeli folk music. The article presents a socio-cultural survey that attempts to answer the following questions: Is the growing involvement with Ladino folk songs in the realm of conservation—in other words, repetition—of the age-old Ladino cultural heritage, or are we witnessing a cultural process whose main thrust is appropriation and whose goal is to use new instruments to bring the cultural wealth from the past into the present and present it to a new generation, not necessarily the current generation of the Sephardic ethnic group?